2023
DOI: 10.1063/5.0141559
|View full text |Cite
|
Sign up to set email alerts
|

Wronskian solutions and Pfaffianization for a (3 + 1)-dimensional generalized variable-coefficient Kadomtsev-Petviashvili equation in a fluid or plasma

Abstract: In this paper, we investigate a (3+1)-dimensional generalized variable-coefficient Kadomtsev-Petviashvili (GVCKP) equation in a fluid or plasma. The Nth-order Wronskian solutions for that equation are derived and proved under certain variable-coefficient constraints, where N is a positive integer. One-, two- and three-soliton solutions in the Wronskian for that equation are given. By means of the Pfaffianization procedure, a coupled (3+1)-dimensional GVCKP system is constructed from that equation. Bilinear for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…As we know, the wave-packet behaviours of both equations cannot be fully determined via the analytical methods, except with certain initial and boundary conditions [3,4,[7][8][9][10][11][12]. Therefore, various conventional meshbased numerical methods have been introduced to explore the Boussinesq and Camassa-Holm equations, such as the finite-element method, the finite volume method and the spectral method [20][21][22][23][24][25][26][27]. It has been revealed that for the Boussinesq equation in the 'good' case, those numerical methods can provide satisfactory results, while for the Boussinesq equation in the 'bad' case, most numerical methods fail due to the instability of the equation, even for the simulation of the simplest bell-shaped solitons [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the wave-packet behaviours of both equations cannot be fully determined via the analytical methods, except with certain initial and boundary conditions [3,4,[7][8][9][10][11][12]. Therefore, various conventional meshbased numerical methods have been introduced to explore the Boussinesq and Camassa-Holm equations, such as the finite-element method, the finite volume method and the spectral method [20][21][22][23][24][25][26][27]. It has been revealed that for the Boussinesq equation in the 'good' case, those numerical methods can provide satisfactory results, while for the Boussinesq equation in the 'bad' case, most numerical methods fail due to the instability of the equation, even for the simulation of the simplest bell-shaped solitons [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It is common knowledge that nonlinear science studies chaos, solitons, and fractals [1,2]. In several areas of nonlinear physics, including hydrodynamics [3][4][5], plasmas [6][7][8], optics [9][10][11] and Bose-Einstein condensates [12][13][14][15][16][17], the study of various nonlinear waves [18][19][20][21][22][23][24][25][26] is a significant issue. Nonlinear waves include breathers, rogue waves, and solitons.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear evolution equations (NLEEs) play an important role in describing the main feature of physical science and engineering areas, such as fluid mechanics [1,2], plasma physics [3,4], hydrodynamics [5,6], optical fibers [7][8][9][10] and chaos theory [11,12]. The solutions of these equations, especially multiwave interaction solutions, can help researchers obtain penetrating insight for some phenomena modeled by the NLEEs.…”
Section: Introductionmentioning
confidence: 99%